Dr. Phil : Self-help Guru and TV Superstar - Main, Mary (Berkeley Heights, NJ : Enslow Publishers, 2008)
Presents a biography of the psychologist and television personality known for his blunt, practical advice.
Midnight meeting -- Country boy -- Taking flight -- Like father, like son -- Becoming Doctor McGraw -- Courtroom wizard -- Counselor and life strategist -- Family fame -- Television guru -- Giving back -- Family first.
Includes bibliographical references and index.
Keywords: McGraw, Phillip C., -- 1950-; Psychologists -- Biography -- United States; Television personalities -- Biography -- United States